Characterization of Pseudomonas aeruginosa LpxT reveals dual positional lipid A kinase activity and co‐ordinated control of outer membrane modification. Issue 3 (30th September 2014) - Nowicki, Emily M.; O'Brien, John P.; Brodbelt, Jennifer S.; Trent, M. Stephen
Summary Gram‐negative bacteria have evolved modification machinery to promote a dynamic outer membrane in response to a continually fluctuating environment. The kinase LpxT, for example, adds a phosphate group to the lipid A moiety of some Gram‐negatives including Escherichia coli and Salmonella enterica. LpxT activity is inhibited under conditions that compromise membrane integrity, resulting instead in the addition of positively charged groups to lipid A that increase membrane stability and provide resistance to cationic antimicrobial peptides. We have now identified a functional lpxT orthologue in P. aeruginosa. LpxTPa has unique enzymatic characteristics, as it is able to phosphorylate P. aeruginosa lipid A at two sites of the molecule. Surprisingly, a previously uncharacterized lipid A 4′‐dephospho‐1‐triphosphate species was detected. LpxTPa activity is inhibited by magnesium independently of lpxTPa transcription. Modulation of LpxTPa activity is influenced by transcription of the lipid A aminoarabinose transferase ArnT, known to be activated in response to limiting magnesium. These results demonstrate a divergent activity of LpxTPa, and suggest the existence of a co‐ordinated regulatory mechanism that permits adaptation to a changing environment.